Genetic and epigenetic uniformity of polyembryony derived multiple seedlings of Hevea brasiliensis - Rekha K; Saha T; Sobha S; Sushamakumari S; Thomas K U; Unnikrishnan D (Protoplasma, 2015)
Hevea brasiliensis Muell. Arg. (Para rubber tree) is a tropical tree species of Amazonian origin widely cultivated in several parts of the world for natural rubber, a highly priced commodity inevitable for the world rubber industry. Large, tree to tree variation in growth and latex yield among individual plants of high yielding Hevea clones is a common phenomenon observed in mature rubber plantations. The genetic heterogeneity of the seedlings which are used as rootstocks for propagation through budgrafting is considered as a major factor responsible for this variation. In order to minimize this variation, attempts were made to develop highly uniform rootstock material via an in vitro technique by inducing zygotic polyembryony in Hevea. Immature open pollinated fruits of a high yielding clone RRII 105 were cultured by half ovulo embryo culture technique. Multiple embryos were induced from the 8-10-week-old zygote with a novel combination of gibberellic acid (GA3), kinetin, and zeatin. Plantlets were successfully generated from the multiple embryos and raised in the field post hardening. Screening using genetic and epigenetic molecular markers revealed that the multiple seedlings developed are highly uniform and are of single zygotic origin. Development of plants having genetic and epigenetic uniformity suggests that this technique is ideal for raising uniform rootstock material in Hevea which may significantly reduce intraclonal variations. Moreover, these plants could serve as ideal material for physiological and molecular investigations towards the understanding of stock-scion interaction process in rubber.
Keywords: DNA methylation; Halfovulo embryo culture; Hevea brasiliensis; Polyembryony; Stock-scion interactions